Pengaruh Green accounting Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Perusahaan Sebagai Variabel Intervening (Studi Empiris Perusahaan Sektor Energi & Industri Periode 2020-2024) - Della Gusvina; Wirmie Eka Putra; Muhammad Ridwan (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The underlying problem of this research is the limited empirical evidence regarding the effectiveness of green accounting implementation in increasing company value, especially when linked to the role of financial performance as an intervening variable. This study aims to analyze the effect of green accounting on company value with financial performance as an intervening variable in energy and industrial sector companies during the 2020–2024 period. The research method uses a quantitative approach with Partial Least Square (PLS) analysis techniques through the SmartPLS application. The research sample consisted of 21 energy and industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 observation period and were selected through a purposive sampling method. The results show that green accounting has a positive and significant effect on financial performance and company value. However, the key finding of this study is that financial performance does not significantly affect company value and is unable to mediate the relationship between green accounting and company value. Thus, although green accounting practices can directly improve financial performance and market perception, this improvement in financial performance does not act as a bridge between the influence of green accounting practices on company value. This finding confirms that investors respond more directly to environmental commitments, rather than through changes in financial performance as an intermediary.